Senyawa-senyawa Oligomer Resveratrol dari Kulit Batang Shorea brunnescens (Dipterocarpaceae) - Haryoto Haryoto; Yana Maolana Syah; Lia Dewi Juliawaty; Sjamsul Arifin Achmad; Jalifah Latip; Euis Holisotan Hakim (Jurnal Matematika & Sains, 2006)
Six resveratrol oligomers, namely (-)- Îµ-viniferin (1), (-)-laevifonol (2), (-)-vaticanol B (3), (-)-hemsleyanol D (4), (+)-isohopeaphenol (5), and (-)-hopeaphenol (6) have been isolated from the acetone extract of the stem bark of Shorea brunnescens. The structure determination of these compounds were based on spectroscopic data (UV, IR, 1H NMR), and compared with literature data. The cytotoxicity of isolated compounds against murine leukemia P-388 cells showed the IC50 values as 18.1, 23.2, 41.9, 12.3, 39.7, and 5.5 ÂµM, respectively.